Seasonal Changes in Preschoolers’ Sedentary Time and Physical Activity at Childcare - Schuna, John M.; Liguori, Gary; Jared Tucker, Jared Tucker (International Journal of Child Health and Nutrition, 2016)
Background: This investigation evaluated seasonal changes in preschoolers’ (3-5 years) sedentary time and physical activity (PA) during childcare. Methods: Sixty-two children from 4 preschools in Fargo, North Dakota had their sedentary behavior and PA objectively assessed during 2 separate weeks of childcare. Children wore accelerometers for 5 consecutive days, once each in the fall (October/November) and winter (January/February). Separate analyses were conducted to evaluate seasonal changes in full-day, indoor only, and outdoor only sedentary time and PA during childcare. Results: When expressed relative to accelerometer wear time, the full-day rate of sedentary time accumulation (minutes/hour) increased significantly from fall to winter (p < 0.001), while accumulation rates for all other PA variables (light PA, moderate PA, moderate-to-vigorous PA, and activity counts) significantly declined during this period (all p’s < 0.001). No significant changes in accumulation rates for sedentary time or PA (light PA, moderate PA, moderate-to-vigorous PA, and activity counts) were noted for either indoor or outdoor time between seasons. Conclusions: Childcare-related sedentary time and PA can dramatically vary across seasons.